Spatial and vertical variation of rhizosphere soil physicochemical and biological properties in Deciduous forests of Bangladesh (Bangladesh Journal of Botany, 2025)
Soil physicochemical and biological properties are key determinants of ecosystem functioning in tropical deciduous forests. This study investigated the spatial and vertical variability of soil characteristics and microbial activity in the Bhawal (BNP) and Madhupur (MNP) Sal forests of Bangladesh. Rhizosphere soil samples were collected from two depths to analyze physicochemical and biological parameters. Two-way ANOVA, correlation, regression, and NMDS analyses were applied to evaluate variation and interrelationships. Significant spatial and vertical differences (p